Complete sternal-sparing left ventricular assist device implantation is associated with improved postoperative mobility. (4th February 2021) - Ayers, Brian C; Bjelic, Milica; Wood, Katherine; Sheen, Soun; Morrison, Eric; Prasad, Sunil; Gosev, Igor
Abstract: Left ventricular assist device (LVAD) implantation via a complete sternal-sparing (CSS) technique is gaining interest due to several potential benefits. We hypothesized that the CSS approach for HeartMate 3 (HM3) LVAD implantation improves postoperative mobility and physical independence compared to full sternotomy (FS). We retrospectively reviewed patients who were implanted with a commercial HM3 at our institution from September 2017 to August 2018. The Activity Measure for Post-Acute Care short forms and Functional Independence Measure scores were used to assess the patient's physical limitations postoperatively. A total of 43 patients were included in the study: 27 (63%) CSS patients and 16 (37%) FS patients. At postoperative day 3, the CSS cohort demonstrated improved mobility based on Activity Measure for Post-Acute Care scores compared to the FS group; 40% of the CSS cohort versus 67% of the FS cohort remained 100% impaired. The CSS cohort also demonstrated greater postoperative independence in the Functional Independence Measure sit-to-stand metric with 78% of the CSS cohort achieving modified or complete independence by postoperative day 15 compared to only 21% of the FS patients. These early data suggest that the CSS approach for HM3 LVAD implantation improves postoperative mobility and functional independence compared to FS.